Penghambatan Respons Etilen pada Mawar Potong Melalui Modifikasi Larutan Perendam, 1-MCP, dan Sitokinin - Syariful Mubarok; . Nursuhud; Erni Suminar; Venny Revia Viola (Jurnal Ilmu Pertanian Indonesia, 2018)
Roses (Rosa hybrida Hort.) are the popular flowering plants in Indonesia, however, some problems on postharvest cut roses are faced, such as short of flower longevities. The freshness or longevity of cut flowers can be maintained for a longer time by using vase solution, inhibition of ethylene responses ie with the use of 1-Methylcyclopropene (1-MCP) and cytokinin. The objective of this study is to determine the effect of 1-MCP and cytokinin combined with in a vase solution on the flower longevity dan quality of cut roses. The experiment was conducted using a Completely Randomized Design consisting of nine treatments, cinsisting of: control; combination of sucrose + NaOCl + cytokines (1% + 0.01% + 20 ppm; 2% + 0.01% + 20 ppm; 1% + 0.05% + 20 ppm; and 2% + 0.05% + 20 ppm) and combination of sucrose + NaOCl + cytokinin (1% + 0.01% + 1 ppm; 2% + 0.01% + 1 ppm; 1% + 0.05% + 1 ppm; and 2% + 0.05% + 1 ppm). The results showed that the composition of 1% sucrose + 0.05% NaCl + cytokinin solution 20 ppm gave the best results in maintaining the angle of petals, reducing the increase of flower diameters, retaining flower petal colors, and making flower longevities up to 11.56 days.